Coupling an electrospray ionization mass spectrometer with a glovebox: A straightforward, powerful, and convenient combination for analysis of air-sensitive organometallics - Lubben, A; McIndoe, J; Weller, A (2008)
The study of highly air- and moisture-sensitive organometallic complexes by ESI-MS is greatly facilitated by interfacing the instrument to an inert-atmosphere glovebox, a modification that requires no special precautions beyond proximity. © 2008 American Chemical Society.